Charles Grimes Bridge Foundations, Melbourne, Australia - Synopsis - Charles Pol Vuillier (Deep Foundations Institute, 2000)
Piling work for modification to the Charles Grimes Bridge in Melbourne, Australia required piles to be installed through 15 to 20 m thickness of very soft to soft silty clay overlying 10 m of stiff clays and sands in turn overlying siltstone. The presence of an old sewer founded at depth in the soft clays demanded that vibrations be kept to a minimum. Two pile type were used by Vibro-pile (Australia) to provide the client with the most economical piling price. The two pile types were CFA piles of 750mm diameter founded in the weathered rock and a full displacement concrete injected screw pile developed by Vibro-pile called the "Z" pile, founded on the rock. The development and features of the "Z" pile are briefly discussed, including the perceived applications and advantages of the pile type. On board instrumentation comprising a computer was used to monitor all aspects of the construction. The rig instrumentation provided an important quality control measure that gave confidence in the pile installed. Pile performance was proved on the cast in situ piles by dynamic load testing methods. Initially tests performed with a 120 kN drop hammer, which was not capable of mobilising the required loads. The performance was then satisfactorily proved by using a drop hammer of 20 tonne mass delivering blows drop heights of 1.5m. Low strain integrity tests on a number of piles were also used to confirm the structural integrity of the piles.